The Use of IV Vasoactive Intestinal Peptide (Aviptadil) in Patients With Critical COVID-19 Respiratory Failure: Results of a 60-Day Randomized Controlled Trial*. Issue 11 (29th August 2022) - Youssef, Jihad Georges; Lavin, Philip; Schoenfeld, David A.; Lee, Richard A.; Lenhardt, Rainer; Park, David J.; Fernandez, Javier Perez; Morganroth, Melvin L.; Javitt, Jonathan C.; Jayaweera, Dushyantha
Abstract : OBJECTIVES: Respiratory failure is a lethal complication of COVID-19 that has remained resistant to drug therapy. Vasoactive intestinal peptide (VIP) is shown in nonclinical studies to upregulate surfactant production, inhibit cytokine synthesis, prevent cytopathy, and block replication of the severe acute respiratory syndrome coronavirus 2 virus in pulmonary cells. The study aims to determine whether Aviptadil (synthetic VIP) can improve survival and recovery in patients with COVID-19 respiratory failure compared with placebo and demonstrate biological effects in such patients. DESIGN: A multicenter, placebo-controlled trial. SETTING: Ten U.S. hospitals: six tertiary-care hospitals and four community hospitals. PATIENTS: A total of 196 patients with COVID-19 respiratory failure. INTERVENTIONS: Participants were randomized 2:1 to receive 3 days of IV Aviptadil or placebo. MEASUREMENTS AND MAIN RESULTS: The primary end point (alive and free from respiratory failure at day 60) did not reach statistical significance (odds ratio [OR], 1.6; 95% CI, 0.86–3.11) for patients treated with Aviptadil when controlling for baseline ventilation status as prespecified in the protocol. There was, however, a statistically significant two-fold odds of improved survival (OR, 2.0; 95% CI, 1.1–3.9) at 60 days ( p = 0.035). There was significant improvement in respiratory distress ratio and reduced interleukin 6 cytokine release ( p = 0.02) by day 3. Subgroup analysis identified a statistically significant likelihood of achieving primary end point among those treated with high-flow nasal oxygen at baseline ( p = 0.039). Subjects on mechanical ventilation also experienced a 10-fold increased odds of survival with drug versus placebo ( p = 0.031). CONCLUSIONS: The primary end point did not reach statistical significance, indicating that there was no difference between Aviptadil versus placebo. However, Aviptadil improves the likelihood of survival from respiratory failure at day 60 in critical COVID-19 across all sites of care. Given the absence of drug-related serious adverse events and acceptable safety profile, we believe the benefit versus risk for the use of Aviptadil is favorable for patient treatment.